Flora of water bodies in the eastern part of the Dnieper-Donetsk depression - Rokytianskyi, A.; Gamulya, Yu. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2021)
The article presents results of the study of flora of the reservoirs in the eastern part of the Dnieper-Donetsk basin. An annotated list of flora was compiled on the base of personal field research, analysis of herbarium materials, and available literature data. The annotated list provides information on the herbarium specimens, species distribution in the study region, its general geographic distribution, habitat ecology, conservation status, life form, economic significance, and known literature references in the study region. It is established that the flora of water bodies of the area in question includes at least 61 species of higher aquatic vascular plants. The family Potamogetonaceae is the most species-rich (18 species, about 30% of the total aquatic flora of the region). The most species-rich genus is Potamogeton (16 species); other taxa are represented by a small number of species. A dominant life form is a group of submerged rooted aerohydatophytes, which numbers 28 species (45.9% of the total flora); the rooted aerohydatophytes with leaves floating on the water surface account for 12 species (19.6%). In terms of geographical distribution, the most abundant is the species group with a circumpolar type of area (28 species). Fourteen species have Eurasian ranges. Other area types are represented by a small number of species. The aquatic flora of the eastern part of the Dnieper-Donetsk basin has a high sozological value. Twenty-six species (42.6% of the flora) have conservation status. The Red Book of Ukraine includes six species, viz. Aldrovanda vesiculosa L., Utricularia intermedia Hayne, U. minor L., Salvinia natans (L.) All., Trapa natans L., and Nymphoides peltate (S.G. Gmel.) Kuntze. Three of them are listed in Annex I of the Berne Convention, and the other three are tertiary relics. Three species are included in the European Red List of Vascular Plants. The list of rare, endangered, typical, and in need of special protection plant groups (Green Book…., 2009) includes 14 aquatic assemblages. Recently, against the background of a general decrease in autochthonous floristic diversity, new invasive species have appeared in the region, behaving aggressively towards the native flora: Pistia stratiotes L. and Eichhornia crassipes (Mart.) Solms.